IMPROVING THE SURVIVAL OF PROBIOTIC IN SIMULATED CONDITIONS AND AZOXYMETHANE-INDUCED COLON TUMOUR BEARING MICE USING MODIFIED CITRUS PECTIN-ALGINATE MICROENCAPSULATION - Odun-Ayo, Frederick; Mellem, John; Reddy, Lalini (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: For a probiotic to be viable it needs to be preserved at a recommended minimum level of 6–7 log10cfu/g in the productbeing consumed, as suggested by the International Dairy Federation. Different biopolymer matrices have been used forencapsulation of probiotic; however, loss of viability is still a challenge.Materials and Methods: Modified citrus pectin-alginate microbeads containing Lactobacillus acidophilus ATCC 4356 wasdeveloped. Efficiency of the microbeads was evaluated in simulated conditions of the gastrointestinal tract and in Balb/c miceinduced with colon tumor. Genomic identification of faecal lactobacilli samples from treated mice was also performed.Results: The Modified citrus pectin-alginate probiotic microbeads significantly enhanced the viability of Lactobacillus acidophilusATCC 4356 compared to the control (p< 0.05) both in vitro and in vivo. Exposure of the modified citrus pectin-alginate microbeadsto 3 hours of simulated gastric juice resulted in 82.7% survival of L. acidophilus ATCC 4356. Also, the number of faecal lactobacilliin the modified citrus pectin-alginate probiotic treated mice increased by 10.2% after 28 days.Conclusion: Modified citrus pectin-alginate is a novel effective means of oral delivery of bacterial cells and bioactive compounds.Modified citrus pectin-alginate can be used in probiotic therapy which may improve the prevention of colon cancer.